Manajemen Pakan dan Analisis Usaha Budidaya Udang Vaname (Litopanaeus vannamei ) pada Lokasi yang Berbeda di Kabupaten Bangkalan dan Kabupaten Sidoarjo - Miftachul Ulumiah; Mirni Lamid; Koesnoto Soepranianondo; M. Anam Al-arif; Moch. Amin Alamsjah; Soeharsono Soeharsono (Journal of Aquaculture and Fish Health, 2020)
Asian white shrimp or can be called vannamei shrimp has the Latin name Litopenaeus vannamei has native habitat in coastal waters and American sea waters. This research was carried out in September 2018 in the Asian white shrimp farming business unit Tanjung Putih Village Sepulu District Bangkalan District and in Penatar Sewu Village Tanggulangin District Sidoarjo Regency. This study population used 3 pond plots in Asian white shrimp culture in Tanjung Putih Village, Sepulu District, Bangkalan District and in Penatar Sewu Village Tanggulangin District Sidoarjo Regency. Sample size is determined from the amount of shrimp fry capacity stocked. The sampling technique was carried out by researchers by following activities in the field, census and visiting respondents directly on the farm or in the farmer's group home to obtain the information and data needed. The results showed that the best feed management was obtained the best results on the 4 sample ponds in Sidoarjo with an average final weight growth rate of 9.73 grams at the first partial harvest, 83% Feed Efficiency, and a 90% survival rate. As for the lowest feed management results obtained in sample ponds 1 Bangkalan with a yield of 6.98% growth, feed efficiency by 71% and survival rate of 86%. As for the results of the analysis of vannamei shrimp aquaculture business at different locations in Bangkalan and Sidoarjo districts, it was concluded that the best Production BEP was obtained in Sidoarjo's 4 sample ponds, amounting to 1427 kg. The best R / C ratio and Payback period is the average sample obtained in Sidoarjo. The conclusion of the best feed management and business analysis results is on the sidoajo sample ponds, the sidoarjo sample shows decent and efficient results.